2020
DOI: 10.1111/resp.13949
|View full text |Cite
|
Sign up to set email alerts
|

Stearic acid attenuates profibrotic signalling in idiopathic pulmonary fibrosis

Abstract: Background and objective: Lipid metabolism dysregulation has been implicated in the pathogenesis of IPF; however, the roles of most lipid metabolites in lung fibrosis remain unexplored. Therefore, we aimed to identify changes in lipid metabolites in the lung tissues of IPF patients and determine their roles in pulmonary fibrosis. Methods: Free fatty acids in the lung tissues of IPF patients and controls were quantified using a metabolomic approach. The roles of free fatty acids in fibroblasts or epithelial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…S4g, h ) of Beas-2B cells. We next analyzed the mRNA expression of SLUG and VIM , which are TGF-β1-induced EMT-related genes 30 , 31 . TPPU significantly inhibited TGF-β1-induced mRNA levels of SLUG and VIM (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S4g, h ) of Beas-2B cells. We next analyzed the mRNA expression of SLUG and VIM , which are TGF-β1-induced EMT-related genes 30 , 31 . TPPU significantly inhibited TGF-β1-induced mRNA levels of SLUG and VIM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies suggested that IPF develops as a result of an aberrant wound healing response after recurrent alveolar injury 2 and that dysregulation of lipid metabolism is involved in the pathogenesis of IPF 6 , 7 , 31 . EETs serve as important antifibrotic lipid mediators in fibrotic diseases such as pulmonary and renal fibrosis 17 , 18 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Shikimic acid, an example of an organooxygen compound, was linked to therapeutic effects in osteoarthritis [135]. Metabolites of other classes, such as succinic and stearic acids, presented an apoptotic effect in T-cell acute lymphoblastic leukemia and antifibrotic activity, respectively [136,137]. Flavonoids and isoflavonoids, such as 7,4 -dihydroxyflavone and glycitin, presented activity against lung diseases [138,139].…”
Section: Branchesmentioning
confidence: 99%
“…ACSL1 plays a key role in fatty acid metabolism. Studies have found that lipid metabolism dysregulation play an important role in the pathogenesis of IPF [44,45]. In addition, the levels of stearic acid (the one of fatty acid) is down-regulated in IPF lung tissues than in control lung tissues, and further study found that stearic acid had anti brotic activity [45].…”
Section: Discussionmentioning
confidence: 98%